The law and economics of intellectual property in the digital age : the limits of analysis - Elkin-Koren, Niva. (Routledge-Cavendish research in intellectual property ;, 2013)
"This book explores the economic analysis of intellectual property law, with a special emphasis on the Law and Economics of informational goods in light of the past decade's technological revolution. In recent years there has been massive growth in the Law and Economics literature focusing on intellectual property, on both normative and positive levels of analysis. The rise of Law and Economics as a dominant methodology in intellectual property scholarship has been accompanied by an increased economic discourse in intellectual property policy debates. The economic approach to intellectual property is often described as a monolithic, coherent approach that may differ only as it is applied to a particular case. Yet the growing literature of Law and Economics in intellectual property does not speak in one voice. The economic discourse used in legal scholarship and in policy-making encompasses several strands, each reflecting a fundamentally different approach to the economics of informational works, and each grounded in a different ideology or methodological paradigm. This book delineates the different economic approaches and analyzes their tenets. It maps the fundamental concepts and the theoretical foundation of current economic analysis of intellectual property law, in order to fully understand the ramifications of using economic analysis of law in policy making and to appreciate the current frameworks' limitations in confronting the challenges of the information revolution. The book addresses the fundamental adjustments in the methodology and underlying assumptions that must be employed in order for the economic approach to remain a useful analytic framework for addressing IPR in the information age. "--